A three-generation model for teleradiology. - Engelmann, U. (IEEE Transactions on information technology in biomedicine)
This paper proceeds from the definition of teleradiology. It identifies three different generations of teleradiology systems and includes those systems that are not regarded as teleradiology systems by the authors. A list of requirements pertinent to users of first-generation teleradiology systems is introduced. Most of the requirements have been realized in a new generation teleradiology system called CHILL.